Research of Microstructure, Friction and Wear on Siliconized Aluminum-Bronze With Different Silicon Powder Ratio - Tian, Feng; Wu, Chunyan; Zhu, Bin; Wang, Liang; Liu, Yong; Zhang, Yisheng (Frontiers in Materials, 2021)
In order to enhance the wear resistance without changing the mechanical properties of the substrate, the aluminum-bronze alloy was siliconized by pack cementation in this paper. Its surface hardness was improved by a certain thickness of siliconized layer. The different processes and their influences on the siliconized layer and the substrate were investigated by changing the ratio of siliconizing powder. The microstructure and phase composition of the siliconized layer was detected and analyzed. Compared with the non-siliconized sample, the hardness of the siliconized layer of 30% Si content is increased by 93.54%, and the average friction coefficient is reduced to 40.38%. The maximum thickness of siliconized layer in the experiment is 200 μm when the silicon powder content is 30%. It can be concluded that surface siliconizing is effective to reduce the friction coefficient of aluminum-bronze and improve wear resistance.